Wetting and Wettability - Aliofkhazraei, Mahmood (IntechOpen, 2015)
On the liquid 's surface, the molecules have fewer neighbors in comparison with the bulk volume. As a result, the energy interaction shows itself in the surface tension. Traditionally, the surface tension can be assumed as a force in the unit of the length which can be counted by the unit of Newton on squared meter, or energy on the units of the surface. The surface tension, implies the interface between liquid and vapor, which is an example of the surface tensions. The equilibrium between these surface tensions, decides that a droplet on a solid surface, would have a droplet form or will change to layer form. This book collects new developments in wetting and wettability science.